Asia's regional architecture : alliances and institutions in the Pacific century - Yeo, Andrew, 1978- (Studies in Asian security., 2019)
During the Cold War, the US built a series of alliances with Asian nations to erect a bulwark against the spread of communism and provide security to the region. Despite pressure to end bilateral alliances in the post-Cold War world, they persist to this day, even as new multilateral institutions have sprung up around them. The resulting architecture may aggravate rivalries as the US, China, and others compete for influence. However, Andrew Yeo demonstrates how Asia's complex array of bilateral and multilateral agreements may ultimately bring greater stability and order to a region fraught with underlying tensions. 'Asia's Regional Architecture' transcends traditional international relations models. It investigates change and continuity in Asia through the lens of historical institutionalism.